Communities and crime: an enduring American challenge - Wilcox, Pamela (Urban life, landscape, and policy, 2018)
Images of community in criminological thought -- Community as socially disorganized -- Community as a system -- Community as the truly disadvantaged -- Community as a criminal culture -- Community as a broken window -- Community as criminal opportunity -- Community as collective efficacy -- Communities and crime: looking ahead